Fault Lines of Refugee Exclusion: Statelessness, Gender, and COVID-19 in South Asia - Roshni Chakraborty; Jacqueline Bhabha (Health and Human Rights, 2020)
Despite widespread recognition of the right to a nationality, statelessness and its attendant vulnerabilities continue to characterize the lives of millions in South Asia. During the onset of the COVID-19 pandemic, when states turned inward to protect their own citizens, refugees and de facto stateless persons found themselves excluded from humanitarian services and health care and were denied the ability to claim rights. Stateless women faced the additional burden of gender-based violence, a hostile labor market, and the threat of trafficking. This paper analyzes gender and statelessness as vectors of exclusion in South Asia, where asylum seekers are neither recognized by law nor protected by social institutions. We argue that citizenship constitutes an unearned form of social capital that is claimed and experienced in distinctively gendered ways. The pandemic has shone a bright light on the perils of statelessness, particularly for women, who face exacerbated economic inequities, the forced commodification of their sexuality, and exclusion from mechanisms of justice.